Castellani, Ana (coord.), Recursos públicos, intereses privados. Ámbitos privilegiados de acumulación. Argentina, 1966-2000 - Eduardo Gálvez (H-Industri@)
Castellani, Ana (coord.), Recursos públicos, intereses privados. Ámbitos privilegiados de acumulación. Argentina, 1966-2000, Buenos Aires, UNSAM Edita, 2012 (191 págs.), ISBN 978-987-1435-41-8.